THE INFLUENCE OF THE PROCESS SKILLS APPROACH ON STUDENT LEARNING OUTCOMES ON THE SUBJECT MATTER OF GEOMETRY OPTICS AND ITS APPLICATION CLASS X AT HIGH SCHOOL STATE 2 PERCUT SEI TUAN Y.S 2021/2022 - Pinondang Hutapea; Nurhaida Nurhaida (Sean Institute, 2022)
This study aims to determine the effect of the process skills approach on student learning outcomes in the subject matter of geometric optics and its application in class XI at Senior High School State 2 Percut Sei Tuan Y.S. 2021/2022. This type of research is quasi-experimental research. The population in the study were all students of class XI, Odd Semester, Senior High School Senior High School State 2 Percut Sei Tuan Y.S. 2021/2022 which consists of 6 classes totaling 216 people. Sampling was carried out by cluster random sampling by taking 2 classes out of 3 classes randomly, namely class XI-2 as the experimental class and class X-1 as the control class, each class consisting of 36 people. The instrument used to determine student learning outcomes is a learning outcomes test in the form of multiple choices with a total of 20 questions. The results of the pre-test test before being given different treatment, namely the value in the experimental class was 27.97 with a standard deviation of 11.57 and the value in the control class was 31.76 with a standard deviation of 11.62. In testing the pretest data for both classes, it was found that the data for both classes were normally distributed, homogeneous and had the same initial abilities. Then they were given treatment, namely the experimental class was taught by learning the process skills approach and the control class was taught by conventional learning approaches. After learning is finished, the post-test is given, the post-test score is obtained with an average result of the experimental class of 80.68 with a standard deviation of 9.87 and the control class of 68.92 with a standard deviation of 10.35. From the post-test data processing results it is obtained that tcount = 5.05 and ttable = 1.668, so that tcount > ttable (5.05 > 1.668) then Ha is accepted, thus there is an influence on the learning outcomes of students who are taught with the process skills approach on the subject matter of geometric optics and its application to class XI Senior High School Statei 2 Percut Sei Tuan Y.S. 2021/2022.